Social Media Usage Deviation and Impact on Muslim Family Dynamics in Makassar City, South Sulawesi - Hanafi, Darmawati; Sabara, Sabara; Patimah, Patimah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
In the digital era, household resilience faces challenges from the influence of social media which triggers problems such as divorce in the family. Therefore, this research aims to reveal facts about the impact of social media on divorce among Muslim families in Makassar City, and provide preventive solutions to counteract this negative influence. This article uses empirical research methods using a legal sociological approach. Data was collected through in-depth interviews and literature study. The informants interviewed were religious court judges and divorced couples. The research location is the Makassar City Religious Court. Meanwhile, the literature referred to is relevant articles, books and references. The results of this research show that social media is the main factor causing divorce in married couples. Likewise, the factors that cause divorce are incompatibility, the presence of a third party (infidelity), domestic violence, economic problems. Therefore, the solution that can be taken to deal with the negative impact of social media which causes divorce is intensive and extensive guidance through the sakinah family counseling program, strengthening ethics based on religious teachings, and mediation interventions providing opportunities to mitigate these negative influences. In the context of legal sociology, the government through the ministry of religion, judges, ulama as social actors and all elements of society must work together to reduce the divorce rate as a deviation due to social media, so that harmony in the household and family resilience can be realized.